RESULT OF THE FORMATION OF STUDENT CHARACTERS IN FULL DAY SCHOOL - Alan Alfiansyah Putra Karo-Karo; Khairul Usman; Liliana Puspa Sari; Ratna Dewi; Benny Aprial Simangunsong (Jurnal Ilmiah STOK Bina Guna Medan, 2020)
This study aims to determine the results of the formation of student character in a full day school. The method used is descriptive quantitative using the ex post facto approach. The population of this research was 117 people and 33 samples were taken using purposive random sampling technique. With data analysis techniques to see the average results of the formation of student characters using a character questionnaire. Based on the results of statistical data that has been done by researchers, students in the Full Day School environment have an average character of 88.21. From these data it can be concluded that students who are in full day school have good character.